2006
DOI: 10.1017/s0954579406060184
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of parental frightened/frightening subtypes in predicting disorganized attachment within a brief observational procedure

Abstract: Following Main and Hesse's hypothesis, several investigators have affirmed that frightened/frightening (FR) as well as particular atypical maternal behaviors are associated with infant disorganized and adult unresolved attachment. Here, for the first time, FR behavior was observed in (a) middle-class father-infant (n = 25) and independent mother-infant dyads (n = 50) and (b) a brief laboratory play session. In addition, relations between disorganization, unresolved attachment, and the six FR system subscales w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
1
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 44 publications
4
88
1
5
Order By: Relevance
“…Dissociation usually involves sudden onset of freezing and losing track of time, which can interfere significantly with mother-child communication and results in poor responsivity and inconsistent parenting. Recent research has suggested that dissociation during parent-child communication is strongly related to attachment insecurity [39,40]. Non significant associations between depressive and traumatic symptoms on child attachment problems may be attributed to consistent parenting despite these symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Dissociation usually involves sudden onset of freezing and losing track of time, which can interfere significantly with mother-child communication and results in poor responsivity and inconsistent parenting. Recent research has suggested that dissociation during parent-child communication is strongly related to attachment insecurity [39,40]. Non significant associations between depressive and traumatic symptoms on child attachment problems may be attributed to consistent parenting despite these symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In a rare study involving fathers (50 mothers, 25 fathers), Abrams, Rifkin, and Hesse (2006) found that caregivers in disorganized attachment relationships with their infants more frequently engaged in anomalous forms of behavior. However, Abrams et al (2006) collapsed mothers and fathers into one group and did not report specifically on the association between atypical paternal behavior and infant-father attachment. Further, to our knowledge, no published study has ever examined the links among fathers' unresolved states of mind, atypical caregiver behavior, and the infant-father attachment relationship.…”
Section: Precursors Of Infant-caregiver Attachmentmentioning
confidence: 99%
“…Empirical support for links between mothers' U/d classification and FR behaviour has been found in an increasing number of studies (Abrams, Rifkin, & Hesse, 2006;Madigan, Moran, & Pederson, 2006;Schuengel, Bakermans-Kranenburg, & van IJzendoorn, 1999) as well as in our own longitudinal sample (Jacobvitz, Leon, & Hazen, 2006). Even more studies have found strong support for links between mothers' U/d attachment classification and disorganised mother-infant attachment in the strange situation (Lyons-Ruth & Jacobvitz, 2008), and at least one study found that maternal FR behaviour mediates the link between mothers' U/d attachment representations and mother-infant disorganised attachment (Schuengel et.…”
mentioning
confidence: 94%